(untitled) (Modern Information Technologies and Innovation Methodologies of Education in Professional Training Methodology Theory Experience Problems, 2011)
In the article examined and analysed modern consisting of legal education of Ukraine. An author examines theways of improvement of quality of legal education and offers the methods of his improvement. The author considers the necessity to introduce into practice innovative technologies, which are directed at the improvement of educational systemand intensification of educational process.